Exploring the Crisis of Cultural Identity as Reflected in Contemporary Manggarai Songs - Yuliantari, Ans Prawati; Moon, Yuliana Jetia; Handoko, Cons Tri (Institut Seni Indonesia Yogyakarta, 2025)
This study aims to identify and analyze forms of cultural identity crisis in contemporary Manggarai songs circulating through social media. The study employs a qualitative approach, utilizing Fairclough's Critical Discourse Analysis method and Bhabha's Cultural Hybridity theory, to examine the relationship between song lyrics, social practices, and the use of cultural symbols. The results of this study indicate that the cultural identity crisis is reflected in ambivalent discourse and the use of traditional symbols in new forms that are inconsistent with their original meanings. Cultural symbols that were once sacred now appear in the context of emotional expression, social humor, and digital entertainment. This phenomenon shows a shift in meaning and function, where society is no longer in a position of established identity, but instead in a space of negotiation between tradition and modernity. Local music in the digital era has become an important arena for responding to social and economic pressures and the influence of media algorithms. This study concludes that cultural expression through songs reflects the dynamics of constantly changing identities. Recommendations for further research include expanding the study to other musical genres or different cultural contexts to understand the transformation of cultural identity in the broader digital landscape.